Afghanistan after 2014 election : US as strategic partner? - Halimullah Kousary (2015)
The aftermath of the Afghan 2014 presidential election confirms two problems of Afghanistan today. Firstly, democracy is at its nascent stage and elections are not without problems. Secondly, Afghanistan is still a fragile country and needs continued engagement of the international community.